2020
DOI: 10.1029/2019wr026332
|View full text |Cite
|
Sign up to set email alerts
|

Pore‐Scale Modeling of Drainage Displacement Patterns in Association With Geological Sequestration of CO2

Abstract: We investigate the immiscible displacement (drainage) of a wetting fluid in a porous medium by a nonwetting fluid using multi-graphics processing unit (GPU) lattice Boltzmann simulations with the aim of better understanding the pore-scale processes involved in the geological sequestration of CO 2. Correctly resolving the dynamics involved in multiphase flow in permeable media is of paramount importance for any numerical scheme. Generally, the average fluid flow is assumed to be at low Reynolds numbers Re av. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 56 publications
1
8
0
Order By: Relevance
“…Zacharoudiou et al. ( 2020 ) also reported that the presence of the surrounding wetting phase films causes snap‐off and disconnection of the invading non‐wetting phase in the narrow‐constricted pore throats.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Zacharoudiou et al. ( 2020 ) also reported that the presence of the surrounding wetting phase films causes snap‐off and disconnection of the invading non‐wetting phase in the narrow‐constricted pore throats.…”
Section: Resultsmentioning
confidence: 98%
“…As a result, thin films of the decane phase coated the grain surfaces and occupied crevices of the porous medium (see yellow circles in Figure 2c), while the non-wetting water phase propagated within the central regions of the narrow throats. Zacharoudiou et al (2020) also reported that the presence of the surrounding wetting phase films causes snap-off and disconnection of the invading non-wetting phase in the narrow-constricted pore throats.…”
Section: Wettability and Pore-scale Fluid Displacement Mechanismsmentioning
confidence: 92%
“…These pore-scale instability events are clearly driven by capillary forces and therefore happen only when capillary forces exceed the viscous force. This means, referring to the Lenormand phase diagram [9], that Haines jumps mostly occur within the capillary fingering domain [14,15]. On the other hand, the regime of viscous fingering, with viscous forces higher than capillary forces, typically implies, at the microscopic scale, a piston-type invasion, driven by high values of the NWP flow and, consequently, of the pressure gradient, this last being responsible for the absence of the stick-slip behavior previously described.…”
Section: Introductionmentioning
confidence: 87%
“…This takes place on the millisecond time scale, achieving flow rates much higher than the injection rate, while the time between consecutive Haines jumps per unit volume is on the order of seconds to tens of seconds (Armstrong et al., 2014; S. Berg et al., 2013). The high flow rates are supplied by local fluid redistribution (S. Berg et al., 2013; Moura et al., 2020), which induces poorly understood non‐local effects (C. F. Berg et al., 2020; Zacharoudiou et al., 2020).…”
Section: Introductionmentioning
confidence: 99%